TI_GERICHTE 52.2018.94 vom 24. Oktober 2017 , Commessa pubblica. Revoca dell'aggiudicazione e annullamento del concorso - TI Tribunale d'appello (2017)
Commessa pubblica. Revoca dell'aggiudicazione e annullamento del concorso